Pengaruh Debt To Equity (DER) Terhadap Return On Asset (ROA) PADA PT. Sepatu Bata, Tbk - Febrianti, Febrianti; Muniarty, Puji; Ovriyadin, Ovriyadin (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to analyse PT. Shoes Bata Tbkl's Return On Assets (ROA) from 2014 to 2023 and find out how the Debt to Equity Ratio (DER) affected it. The firm is having issues, as shown by the fact that its financial position is going through oscillations and a decrease in total assets and net profit. This is the backdrop to the study. This study makes use of quantitative methods of an associative kind. Secondary data is sourced from the company's yearly financial reports and is analysed using tools such as t-test, correlation coefficient, determination coefficient, and basic linear regression analysis. According to the study findings, Return on Assets (ROA) is significantly and negatively affected by the Debt to Equity Ratio (DER), with a regression coefficient of -0.123 and a significance level of 0.000 (p < 0.05). With a coefficient of determination of 0.535, we may deduce that ROA accounts for 53.5% of the variation in DER and that other, exogenous variables account for the remaining 46.5%. The bottom line is that ROA often falls when DER rises for a given organisation. This demonstrates how the inability to fully use assets to generate profits is a direct result of the company's heavy reliance on debt.